Algorithms and architectures for parallel processing : 16th International Conference, ICA3PP 2016, Granada, Spain, December, 14-16, 2016, proceedings /: 16th International Conference, ICA3PP 2016, Granada, Spain, December, 14-16, 2016, proceedings. (2016) - Unknown
No abstract available